Stabilizing Co4+ Ions in Ultrathin Cobalt Oxide Nanosheets for Efficient Oxygen Evolution Reaction. Issue 21 (5th October 2018) - Wang, Jianghao; Li, Liping; Li, Jing; Meng, Lingshen; Xue, Chenglin; Li, Guangshe
Abstract: Stabilizing transition metal ions with high valence states in two‐dimensional materials is a promising way to enhance electrocatalytic activity for oxygen evolution reaction, but still remains challenging. In this work, we initially report on a synthetic strategy that combines etching and ion‐exchange processes to prepare ultrathin cobalt oxide nanosheets containing Co 4+ ions. The presence of Co 4+ ions makes Co−O bond more covalent, which is essential for adsorption of OH −, but also reduces the charge transfer resistance. Moreover, nanosheets thus prepared provided a large number of active sites for oxygen evolution reaction. Owing to these merits, these nanosheets exhibited an apparently superior activity towards oxygen evolution reaction, delivering an anodic current density of 10 mA cm −2 at 1.57 V (vs RHE), about an order of magnitude higher than that of cobalt oxide nanosheets without Co 4+ ions and bulk LiCoO2 . Further, the repeated availability of the optimized nanosheets for oxygen evolution reaction is excellent: the overpotential at about 10 mA cm −2 was retained in between 340 and 346 mV after continuous cycling for 5000 cycles. Abstract : COERced to be active : Ultrathin cobalt oxide nanosheets containing Co 4+ ions are prepared successfully for the first time, and it exhibit a substantially enhanced catalytic activity for oxygen evolution reaction